Health evaluation of free-ranging and captive pichis (Zaedyus Pichiy; Mammalia, Dasypodidae), in Mendoza province, Argentina - Superina, Mariella (2009)
The health of free-ranging and captive pichis (Zaedyus pichiy) was assessed in Mendoza Province, Argentina, between November 2001 and December 2006. Postmortem examinations of 150 confiscated and vehicle-killed pichis and clinical examinations of 139 wild-caught individuals suggest that the wild populations are currently in good health. Lesions and scars were observed in a large proportion of wild-caught pichis. The most common lesions were associated with parasitism or parasite larva migration. Sarcocystis cysts were relatively common in the skeletal muscle, and Besnoitia cysts were observed in the lungs of 24 evaluated animals. Elevated ambient humidity levels often caused moist dermatitis with epidermal detachment in captive pichis. This report constitutes the first health evaluation of free-ranging and captive Z. pichiy. It will be a starting point for future health studies and will be beneficial for the captive management of this species.